Broad-scale relationships between shorebirds and landscapes in the southern Great Plains - Albanese, Gene; Davis, Craig A. (My University, 2013)
Stopover use by migrating shorebirds is affected by patch-level characteristics of habitat, but the relative influence of broad-scale factors is poorly understood. We conducted surveys of ten 10-km-radius landscapes in north-central Oklahoma from 2007 through 2009 to examine the influence of the amount and composition of wetland habitats and surrounding land cover on shorebird use during migration. We used generalized linear modeling and an information-theoretic framework to identify factors that best explained species richness, total abundance, and abundance of four groups of shorebirds classified by breeding status and migration distance. Total abundance and richness both increased with the area of wetland habitat within a landscape, regardless of the composition of semi-natural and developed land cover surrounding wetlands. Abundance of shorebird species with different migration strategies varied in relation to the composition of wetland types within a landscape. The amounts of various permanent and semi-permanent wetlands best explained abundance of resident species. Short-distance migrant abundance was best explained by the amount of permanent lacustrine wetlands. The amounts of temporary and semipermanent floodwater habitats were important predictors for abundance of intermediate- and long-distance migrants, although permanent riverine habitats were also important for intermediate-distance migrants. Shorebird species richness was best explained by the amounts of floodwater habitats and permanent riverine wetlands. Broad-scale studies thus provide important insights on use of stopover habitats by migratory shorebirds. Within this region, conservation of riverine habitats with a large complement of ephemeral habitats is necessary to provide the stopover habitat for migrating shorebirds.
Keywords: Avian migration; Habitat use; Landscape composition; Landscape ecology; Prairie wetlands; Stopover; Wetland cluster